The Impact of Old Age Pension on Subjective Well-being: Evidence from Thailand - Wornyordphan, Yada; Damrongplasit, Kannika (Journal of Contemporary Social Sciences and Humanities, 2025)
In this study, an analysis was conducted on the impact of old age pension on subjective well-being in Thailand for those aged 60 and over. Data was obtained from the Health, Aging, and Retirement in Thailand (HART) survey for the 2015 and 2020 waves. A random-effects ordered logit model was employed as the primary method due to the panel structure of the data, while the ordered logit model was used as an alternative methodology. The results indicated that the old age pension has a minimal impact on subjective well-being, relative to other non-financial factors. Other variables such as age, marital status, residential area, region, health status, and income perception tend to have stronger impacts on subjective well-being. Subjective well-being decreases with age. Marriage, living in urban areas, better health status, and higher perception of income are associated with improved subjective well-being. Interestingly, the findings from this study also demonstrate regional differences in subjective well-being.